Application of Motor Development Scale: an integrative review - Santos,Maria Cecilia Souza (2019)
ABSTRACT Objective: to know, understand, and analyze studies that employed the Motor Development Scale as a method for motor evaluation. Methods: the study included the databases Scielo, Pubmed, Lilacs, Science Direct, Web of Science, Scopus and Cochrane to identify the studies, using the following keywords: child; motor skills; motor skills disorders. The methodological quality of cross-sectional studies was analyzed by the Loney scale, cohort and case-control studies were assessed by the Newcastle-Ottawa scale, and clinical trials by the Physiotherapy Evidence Database. Results: twenty studies met the inclusion criteria. There was predominance of cross-sectional studies, which had as main outcome the analysis of motor development of schoolchildren, children with obesity and overweight, premature, with Attention Deficit Hyperactivity Disorder, learning disabilities and Down syndrome. The studies presented objective criteria to measure the outcome and for interpretation and applicability of adequate results, although they did not reach the minimum score established by the assessment scales. Conclusion: the Motor Development Scale is being used in Brazil in several contexts, presenting clear and statistically consistent results, although the methodologies of studies do not fully meet the standards of methodological quality.